ENT 600: Ultra Detector Branula (UDB) / Che Wan Kasmiza Che Wan Ahmad … [et al.] - Che Wan Ahmad, Che Wan Kasmiza; Ismail, Norliza; Shukri, Nurul Mawaddah; Abu Hanifah, Syafawati (2018)
Peripheral intravenous cannulation is a common invasive procedure done in hospitals. Although a minor invasive procedure, it has the potential to introduce infection into the local tissue at site of cannulation or directly into the blood stream. However, due to some limitations and constraints, from this current canula, to prevent infection. Thus, in New Product Development (NPD) report, we came out with a solution to this problem which is by developing blueprint by using Ultra Detector Branula (UDB). UDB is the newly created iv canula, to facilitate the physician inserting the line in the peripheral of the child, as well as facilitate the nurse to apply during intravenous medication. Ours companies name WiLS SDN.BHD, we are choosing this name because it gives the meaning of all members. One of our greatest joys at WiLS is hearing our members tell the stories of the big and important work they are doing - interesting new projects or initiatives, or even interesting and new approaches to old projects. And, in addition to hearing about it, it makes us even happier when we can share those stories with other members. WiLS SDN.BHD located at Pandan Indah 55100, Kuala Lumpur.